2004
DOI: 10.1158/0008-5472.can-04-1987
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Is a Reservoir for CD4+CD25+ Regulatory T Cells that Traffic through CXCL12/CXCR4 Signals

Abstract: CD4؉ CD25 ؉ regulatory T cells (Tregs) mediate peripheral T-cell homeostasis and contribute to self-tolerance. Their homeostatic and pathologic trafficking is poorly understood. Under homeostatic conditions, we show a relatively high prevalence of functional Tregs in human bone marrow. Bone marrow strongly expresses functional stromal-derived factor (CXCL12), the ligand for CXCR4. Human Tregs traffic to and are retained in bone marrow through CXCR4/CXCL12 signals as shown in chimeric nonobese diabetic/severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
341
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(373 citation statements)
references
References 39 publications
24
341
1
7
Order By: Relevance
“…CXCL12 can induce chemotaxis of Tregs. 22 Correlation between Treg infiltration and CXCL12 expression has been found in cervical cancer. 23 Classical Tregs inhibit T cells in lymphoid organs.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12 can induce chemotaxis of Tregs. 22 Correlation between Treg infiltration and CXCL12 expression has been found in cervical cancer. 23 Classical Tregs inhibit T cells in lymphoid organs.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%
“…These changes may mobilize Tregs from the bone-marrow reservoir to the periphery. 22 PRIMARY TUMORS AFFECT PREMETASTATIC TISSUES Although metastatic outgrowth of tumor cells is abrogated in CD4-null conditions, including the RAG knockout, which attenuated EGF receptor-mediated activation of metastatic potential of primary tumor cells, we still do not know the mechanisms of the last three steps in metastasis: extravasation, recruitment and regrowth in the lungs. 24 Less than 1% of recruited tumor cells appear to achieve regrowth.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%
“…It has been reported that CD4 ϩ CD25 ϩ or FoxP3 ϩ Tregs express CCR4, CCR5, CCR7, CCR8, CCR10, CXCR4, and CXCR5 and L-selectin, E-selectin, and P-selectin ligands (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). CD103 ϩ Tregs express effector/memory-type trafficking receptors, and CD103 Ϫ Tregs express lymphoid tissue homing receptors (20).…”
mentioning
confidence: 99%
“…Therefore, Treg cells appear not to directly stimulate the differentiation of hematopoietic progenitors into B cells. In contrast to the lack of effect of Treg cells, the addition of activated CD4 + [12]. We found that the K/Bsf BM harbored more CD4 + T cells than the K/B BM, and most of them retained memory/activated phenotypes (data not shown).…”
Section: Treg Cells Protect B Lymphopoiesis By Controlling the Supprementioning
confidence: 73%